USING AUDIOVISUAL MATERIALS IN THE DEVELOPMENT OF LINGUISTIC COMPETENCIES - Khamida Erkinova (Western European Studies, 2025)
This article analyzes the importance of using audiovisual materials in the development of linguistic competencies. Linguistic competence includes the skills of using language not only correctly, but also effectively and purposefully in the teaching process. Today, the increasing role of audiovisual materials in the education system is seen as an effective tool for increasing students' motivation in learning a language, developing their listening, speaking, writing and reading skills. The article analyzes the role of audiovisual materials in language learning, their effectiveness in developing linguistic competencies, as well as their impact on the process of students' language acquisition. Audiovisual materials, including videos, audio lessons, multimedia, interactive games and other materials, effectively develop students' skills such as listening, understanding, thinking and correct expression of speech. Audiovisual materials also help students improve their ability to use language in practice, understand the context of the language in real life.
Keywords: Linguistic competence; audiovisual materials; educational technologies